Komunikasi Visual Perancangan Kemasan Kue Akar Kelapa berdasarkan Unsur-unsur V.I.E.W - Limbong, Edo Galasro; Pratama, Febrian Adi (Magenta | Official Journal STMK Trisakti, 2019)
The culinary industry is a business that is in great demand, from the community to celebrities. The culinary industry that is currently developing is cakes and bread. Many cakes are on the market, there are traditional cakes to various modern cakes. The number of modern cakes is growing, making traditional cakes increasingly less well known by the public, especially for teenagers. One of them is akar kelapa cake. This traditional cake comes from the Betawi region. This cake is usually served during Eid or family events. Though, akar kelapa cake can be used as a daily snack because it does not use preservatives. However, this cake is increasingly unpopular because of the lack of promotion and the form of packaging used looks outdated because it is wrapped in clear plastic. Therefore, to re-attract the interest of the community, one way is to make akar kelapa cake packaging using elements of V.I.E.W. So that it can attract attention and the coconut root cake is again known. The research method used is qualitative with the approach to the process of creating the work. So the output produced is a coconut root cake package. Data collection techniques are conducting observations and literature studies.